2011
DOI: 10.1080/10871209.2011.606521
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to Wolves and Wolf Policy Among Ojibwe Tribal Members and Non-tribal Residents of Wisconsin's Wolf Range

Abstract: Gray wolf (Canis lupus) policy is dynamic and involves multiple stakeholders.Attitudinal surveys have historically measured stakeholder attitudes, although Native American views have rarely been studied systematically. We sent a mail-back questionnaire to members of the Bad River Band of the Lake Superior Tribe of Chippewa Indians (Ojibwe) to assess attitudes toward wolves and Wisconsin wolf policy. We compared their responses to a sample of non-tribal residents of Wisconsin's wolf range. Tribal respondents he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
0
32
2
Order By: Relevance
“…We acknowledge that other factors such as species identity and life history (e.g., large felids vs. rodents, K‐ vs. r‐selected species), cultural traditions (e.g., Shelley et al . ), experience (Kaltenborn et al . ), emotions (Vaske et al .…”
Section: Wildlife Management Matrixmentioning
confidence: 99%
See 3 more Smart Citations
“…We acknowledge that other factors such as species identity and life history (e.g., large felids vs. rodents, K‐ vs. r‐selected species), cultural traditions (e.g., Shelley et al . ), experience (Kaltenborn et al . ), emotions (Vaske et al .…”
Section: Wildlife Management Matrixmentioning
confidence: 99%
“…1998), and education (Shelley et al . ) can influence acceptability of wildlife management actions. However, to illustrate an idealized interaction between changes in wolf management authority and public attitudes toward lethal control options we assume that perceptions of wildlife populations and risk of human–wildlife conflict can be used to identify a range of management actions that would be acceptable to different groups (e.g., the residents of Wisconsin; Figure ).…”
Section: Wildlife Management Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…An early meta‐analysis of 37 data sets spanning 1972–2000 showed attitudes towards wolves correlated negatively with age, rural residence, and agricultural occupation; and positively with education, income, and living outside wolf range (Williams et al , ; see for Europe more recently, Dressel et al , ). People active near wolves expressed more negative attitudes than those more insulated by distance, livelihoods, or pro‐wolf world‐views (Naughton‐Treves, Grossberg & Treves, ; Karlsson & Sjöström, ; Heberlein & Ericsson, ; Shelley, Treves & Naughton‐Treves, ). Recent reviews confirmed that attitudes to wolves were more positive outside wolf range than inside it, both in the U.S.A. and in Europe (Bruskotter et al , ; Dressel et al , ).…”
Section: Human Attitudes To Predatorsmentioning
confidence: 99%